Stochastic Non-Newtonian Lubrication in Roller Bearings Considering Viscosity Variation and Thermal Effects - M. Ganapathi; S. Vijayakumar Varma; K. R. K. Prasad; V. Bharath Kumar (International Journal of Mathematics And its Applications, 2018)
In this paper the generalized Reynolds equation derived for power law fluid is applied to study the squeeze film lubrication of parallel plates considering surface roughness, viscosity variation and thermal effects. The consistency of the lubrication is assumed to vary across the film as two layer fluid and thermal effects by introducing a thermal parameter p in the consistency. Stochastic theory is applied to study roughness effect. Two types of roughness transversal roughness and longitudinal roughness are recognized and expected values of load capacity and time of squeezing are obtained. For all flow behavior index n the effects of high consistency near periphery on these parameters are also studied for both types of roughness.